The Performance of Elastographic Diagnostic of Breast Tumor in Dr. Soetomo Teaching Hospital Surabaya (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Elastography in breast cancer cases has not become a routine examination that is conductedin the radiodiagnostic unit in Dr. Soetomo Teaching Hospital Surabaya. These last few years, elastographyhas been an addition examination modality which is promising to assess breast lesions that are detectedbyan ultrasound. Objective: The aim of the present study is to observe the performance of elastography inbreast tumor cases. Method: This cross-sectional study was conducted in Dr. Soetomo Teaching HospitalSurabaya. The elastography is applied in 65 females (the average age is 49,1 years old) and it was found66 lesions with a definitive diagnosis (34 benign tumors, 32 malignant tumors) which was proved througha fine-needle aspiration biopsy. The grayscale result is classified into benign and malignant categorizationswith examining five descriptors including shape, margin, orientation, echo pattern, and posterior features.Results: The elastography score showed that the sensitivity is 87,5 %, the specificity is 94,1 %, and theaccuracy is 90,9 % The stain ratio showed 93,8 %, 94,1 %, 90,9 % in sequence. On the other hand, thegrayscale result showed 96,9 %, 91,2 %, and 95,5 %. The combination of elastography and grayscale showeda better performancewith the 97,1% of sensitivity, 94,1 % of specificity, and 93,8 % of accuracy. There wasa significant correlation between the lesion size and the quality of elastography result (P = .034) while therewas no correlation with the lesion depth (P = .624). Conslusion: The combination of elastography andgrayscale have a better diagnostic performance in distinguishing benign breast tumor with malignant breasttumor.